Stigma Media terhadap Fandom Perempuan dalam Pemberitaan Penggemar K-Pop - Imamatul Silfia; Rizaludin Kurniawan (Program Studi Ilmu Komunikasi, 2022)
Stigma towards female fandoms is a form of gender discrimination caused by patriarchal culture domination. Such stigmas appear frequently in daily lives, including media. This study was aimed to analyze the stigmatization of K-Pop female fandoms in CNNIndonesia.com and how text discourse plays a role in constructing the representation of female fandoms in the media. This research used Sara Mills Discourse Analysis methodology. The results of this research suggested that there were discriminations to female fandoms in news broadcasted by CNNIndonesia.com. The news in this channel had a tendency to enhance the stigma towards female fandoms through figure of speech and the positioning of subject and object in the media. This news channel also tended to portray female fans as crazy fanatics who have psychological issues and act senselessly.